2021
DOI: 10.1007/s13193-021-01316-6
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Personnel Protective equipment’s (PPE) Use and Comfort Levels Among Surgeons During Routine Cancer Surgery in the COVID-19 Pandemic

Abstract: Personnel protective equipment (PPE) are recommended during surgery even in COVID-19 negative patients especially in a highprevalence region due to its higher false-negative rates. However, the use of PPE has not been universal mainly due to the perception of discomfort and associated stress and fatigue. This study was done to understand the pattern of PPE use by cancer surgeons during the pandemic and the associated discomfort, stress, and fatigue with its use. The survey, consisting of 29 questions, was circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…This study reported that those who interacted with those who wore PPE experienced negative impacts on their psychological health, with increasing levels of anxiety. Additionally, four articles assessed for psychological factors and described similar findings (Kratzke et al 2021 ; Sakuma and Ikeda 2021 ; Thiagarajan et al 2021 ; Wong et al 2013 ). PPE that occluded a part of the face resulted in negative psychological impacts, specifically increasing stress, fatigue, and perceiving someone who wore PPE in a more negative light.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…This study reported that those who interacted with those who wore PPE experienced negative impacts on their psychological health, with increasing levels of anxiety. Additionally, four articles assessed for psychological factors and described similar findings (Kratzke et al 2021 ; Sakuma and Ikeda 2021 ; Thiagarajan et al 2021 ; Wong et al 2013 ). PPE that occluded a part of the face resulted in negative psychological impacts, specifically increasing stress, fatigue, and perceiving someone who wore PPE in a more negative light.…”
Section: Resultsmentioning
confidence: 84%
“…Most of these articles assessed the impact on speech intelligibility, facial and emotion recognition, and listening effort when PPE is worn. Studies also evaluated the impact on psychological health factors, such as stress, fatigue, and emotional state (5 articles, 19%) (Hoedl et al 2020 ; Kratzke et al 2021 ; Sakuma and Ikeda 2021 ; Thiagarajan et al 2021 ; Wong et al 2013 ). Two articles investigated the effect of PPE use on psychological illness symptoms, specifically anxiety and depression (2 articles, 8%) (Emanuel et al 2017 ; Tavakolizadeh et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the COVID-19 outbreak, medical staff had headaches due to the use of masks. In addition, symptoms, such as shortness of breath, sleep disorders, and fatigue, increased significantly ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%